Investigation of Relation between Organizational Culture and Organizational Commitment in Libraries Personnel of University of Tehran: Based on Dennison’s Organizational Culture Model - Mohammad Sadegh Ziaee; T Roshandel Arbatani; abbas nargesian (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2011)
Objective: The present study aim is to explain relationship between Dennison’s organizational culture and personnel organizational commitment. Methodology: This is a practical research whose data was collected through survey. The correlation between variables, however, was based on structural equation modeling. Statistical population of this research includes Libraries Personnel of University of Tehran. Findings: Research findings based on structural equation modeling portend that there is meaningful relationship between organizational culture and promoting of organizational commitment. Also, there is a positive and meaningful relationship between dimension of organizational culture (involvement, consistency, adaptability, and mission) and organizational commitment